A simple HPLC method for the simultaneous determination of venlafaxine and its major metabolite O-desmethylvenlafaxine in human serum. (August 2011) - Samanidou, Victoria; Nazyropoulou, Chrysa; Kovatsi, Leda
Venlafaxine is a very popular antidepressant in Greece. There is an increasing rate of self-poisoning cases with this drug presenting at the emergency departments around the country. We have developed a simple HPLC method with ultraviolet detection for the simultaneous determination of venlafaxine and its major metabolite, O -desmethylvenlafaxine, in human serum following solid-phase extraction. The developed method was validated in terms of sensitivity, linearity, accuracy, precision, stability and selectivity both for therapeutic and toxic serum ranges, and was applied to human serum samples. The method currently developed and validated is simple, does not require expensive instrumentation and can therefore be easily applied in the clinical toxicology setting for the diagnosis and management of acute venlafaxine intoxication.